Church dispensation legislation - ZABOROWSKI, MAREK (Prawo Kanoniczne, 2013)
The institution of dispensation has evolved since the beginnings of the Church. It has taken various forms, but it has always aimed at loosening the law in a particular case. The Church has changed or moderated its rules and regulations depending on the circumstances. Such loosening of church regulations in particular cases in the primal (original) Church typically took place in order to ensure the valid and decent continuity of what had initially been done unlawfully. In time dispensation was given also before performing some acts, allowing what – according the church rules and regulations – had been forbidden. Each law has as its aim first of all the common good, which is the good of the general public. However, a community consists of individual persons, for whom a particular law may turn out to be too burdensome, causing harm or hindering an individual’s achieving of the greater good. Dispensation serves the purpose of dealing with such conflicting situations. It has the capacity of a correcting standard (norm) in cases, in which natural rightness requires a competent authority to suspend to some extent for an instant the effectiveness of a given church law. The above article presents the evolution of the institution of dispensation over a span of the Church’s history. It discusses the reasons which make a church legislator loosen a law in particular cases; it also discusses the effects of dispensation.